2008
DOI: 10.1016/j.jhep.2008.01.006
|View full text |Cite
|
Sign up to set email alerts
|

The function of serotonin within the liver

Abstract: Serotonin or 5-hydroxytryptamine (5-HT) is known to regulate several key aspects of liver biology and these functions include hepatic blood flow, innervation and wound healing. Given the importance of these functions it is surprising that relatively little time has been dedicated to studying the precise function and mechanisms of serotonin within the liver. Here we describe what is known about serotonin and the liver and those receptor types that mediate the observed effects with an aim to stimulating new inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
124
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(131 citation statements)
references
References 47 publications
6
124
0
1
Order By: Relevance
“…8,[13][14][15][16] Therefore, in this study, we used these agents to investigate the involvement of 5-HT 2 receptor subtypes and their intracellular signal transduction pathways in 5-HT-induced hepatocyte DNA synthesis and proliferation in primary cultures of adult rat hepatocytes.…”
Section: -7)mentioning
confidence: 99%
See 1 more Smart Citation
“…8,[13][14][15][16] Therefore, in this study, we used these agents to investigate the involvement of 5-HT 2 receptor subtypes and their intracellular signal transduction pathways in 5-HT-induced hepatocyte DNA synthesis and proliferation in primary cultures of adult rat hepatocytes.…”
Section: -7)mentioning
confidence: 99%
“…5-HT mediates a diverse array of responses-including platelet aggregation, vascular constriction, and cell proliferation-by interacting with 5-HT receptor subtypes in mammals. 8) Seven receptor classes including 14 subtypes of 5-HT receptors have been identified to date, reflecting the diversity of 5-HT actions. With the exception of the 5-HT 3 receptors, which are ligand-gated ion channels, all known 5-HT receptors are G-protein-coupled receptors that are positively linked to phosphatidylinositol turnover or cyclic AMP production and are further linked to a variety of downstream pathways.…”
mentioning
confidence: 99%
“…However, the aforementioned experimental models involved both the central and the peripheral serotonergic system. It is noteworthy that 90% of serotonin is produced in enterochromaffin cells located in the gastric mucosa and taken up by platelets that transport it to an appropriate site, e.g., the adrenal and thyroid glands or the liver, where it can affect the proliferative capacity of hepatocytes (Ruddell et al, 2008). Therefore, systemic administration of the aforementioned substances (PCA or PCPA) or a tryptophan-free diet must have also affected the peripheral serotonin pool and its action on the peripheral secretory glands and the liver.…”
Section: Tablementioning
confidence: 99%
“…Since our present results, obtained after damage to the brain serotonergic system, are different from those reported after general serotonin reduction, it is suggested that peripheral serotonin may also contribute to the regulation of cytochrome P450 in the liver by affecting the enzyme in a different way. It has been found that serotonin receptors are also present in the pituitary (Abrahamson et al, 1987;Dinan, 1996;Balsa et al, 1998;Papageorgiou and Denef, 2007), adrenal gland (Lefebvre et al, 1998), thyroid gland (Csaba and Richter, 1975;Lychkova, 2013), and the liver (Ruddell et al, 2008), where they may affect the release of pituitary hormones (GH, adrenocorticotropic hormone, TSH), corticosterone, or Fig. 6.…”
Section: Tablementioning
confidence: 99%
“…5-HT mediates many types of biological responses such as platelet aggregation, vascular constriction, and cell proliferation and mediates a diverse array of responses by interacting with 5-HT receptor subtypes in mammals. 6) Seven receptor classes including 14 subtypes of 5-HT receptors have been identified, reflecting the diversity of 5-HT actions. With the exception of the 5-HT 3 receptors, which are ligand-gated ion channels, all known 5-HT receptors are G-protein-coupled receptors that are positively linked to phosphatidylinositol turnover or cAMP production and further linked to a variety of downstream pathways.…”
mentioning
confidence: 99%